Model-Model Pembelajaran Mahārah Al-Istimā’ dan Mahārah Al-Kalām di Pesantren Mahasiswa An Najah Purwokerto - Hanifah, Yuyun; Safii, Randi; A. Hasan, Adtman (Language Development Center, 2024)
Background: This research was conducted due to interest in the learning of the Arabic language at the An-Najah student Islamic boarding school in Purwokerto, especially in the Foreign Language complex called the An-Najah Arabic Javanese English Community (AArJEC). There, the students appeared happy to learn because of the teacher's creativity in teaching, which helped them understand the Arabic language easily. Purpose: The purpose of this study is to describe the learning models of mahārah al-istimā' and mahārah al-kalām at the An-Najah Student Islamic Boarding School in Purwokerto. Method: This research employs a descriptive qualitative research approach to investigate the Learning Model of mahārah al-istimā' (listening skills) and mahārah al-kalām (speaking skills), with data sources obtained from students at the An-Najah Islamic Boarding School in Purwokerto. The data collection process involved interviews, participatory observation, and documentary study, with data analysis techniques including data reduction, data presentation, and verification. Results and Discussion: The research findings show that the learning models used for mahārah al-istimā' were the niteni (observing) model and the translation model. As for the Mahārah al-kalām learning models, they included the free conversation model as well as language activity models such as khitabah (public speaking), theatre, and Arabic discussion forums. Conclusions and Implications: The learning of mahārah al-istimā' and al-Kalam at the An-Najah Islamic Boarding School utilizes the Niteni and Translation models, which combine active listening, vocabulary acquisition, and contextual understanding. These findings can be considered in the development of Arabic language curriculum and teaching methodologies.